Two peculiar new species of Otites Latreille 1804 (Diptera: Ulidiidae) with reduced phallus - Morgulis, Elizabeth (Zootaxa, 2015)
Two new closely related species of the genus Otites are described and illustrated: O. freidbergi n. sp. from Israel, and O. friedmani n. sp. from Cyprus. The two species exhibit unusual male terminalia for Otites and other Otitini. Laboratory behavioral observations on live O. freidbergi individuals showed unusually long copulation duration compared to other examined Otitini species.